Letter to Mayor Robert Pena from Mayor Tsujio Kato - Tsujio Kato:::Mayor, City of Oxnard::: (1976)
A letter discussing the possibility of joining the city of Camarillo and the County of Ventura in proposed airport meetings due to the impact the meetings would have on the city of Oxnard.